2001
DOI: 10.1002/sim.984
|View full text |Cite
|
Sign up to set email alerts
|

A method to assess the proportion of treatment effect explained by a surrogate endpoint

Abstract: Randomized clinical trials are the standard for evaluating new drugs, devices and procedures. Traditional clinical trials entail not only considerable expense, but require considerable time to complete. The use of surrogate endpoints constitutes an effort to control cost and completion time for clinical trials. We propose a method to quantify the proportion of treatment effect explained by a surrogate endpoint based on a general model setting which includes the commonly used linear, logistic and Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 18 publications
1
73
0
Order By: Relevance
“…Using the method of Li and Meredith, we estimated the proportion of the effect of CEE + MPA on breast cancer risk that was explained by new-onset breast tenderness 24 . Using the incidence estimates of new-onset breast tenderness and the parameter estimates from a Cox proportional hazards model, this formula calculated the proportion of the treatment effect explained by the surrogate marker, new-onset breast tenderness, divided by the overall effect of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Using the method of Li and Meredith, we estimated the proportion of the effect of CEE + MPA on breast cancer risk that was explained by new-onset breast tenderness 24 . Using the incidence estimates of new-onset breast tenderness and the parameter estimates from a Cox proportional hazards model, this formula calculated the proportion of the treatment effect explained by the surrogate marker, new-onset breast tenderness, divided by the overall effect of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…To control the variability, each study was simulated 100 times to generate the IPD. We considered these two values since 3.2% was the average BMD increase over placebo across all studies (Li et al, 2001) and 8% BMD increase over placebo was used by Wasnich and Miller (2000). Specifically, we applied a Poisson regression model to estimate the association between BMD and fracture risk reduction.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical trials that reported a reduction in fracture risk also increased BMD significantly, although the fracture risk reduction appeared not to be linearly proportional to the BMD increases. For risedronate, Li et al (2001) conducted an analysis using IPD from the two vertebral fracture trials (Reginster et al, 2000;Harris et al, 1999) and reported that 28% of the vertebral fracture risk reductions was explained by BMD increase. However, the corresponding BMD increases over placebo were 6.2%, 5.8%, and 2.7%, reflecting a wide range of BMD response from agent to agent.…”
Section: Motivating Example: Fracture Risk Reduction Explained By Bmdmentioning
confidence: 99%
See 2 more Smart Citations